The Law Enforcement in Judges' Decisions based on Progressive Law - Eko Hartoyo; Widayati Widayati; Ira Alia Maerani (Universitas Islam Sultan Agung, 2022)
This study aims to identify and examine law enforcement in judges' decisions based on progressive law. This study uses a normative juridical approach with descriptive analysis. The data used was secondary data obtained through literature study, which was then analyzed qualitatively. Based on the research, it is concluded that law enforcement in fair judge decisions is based on progressive law, namely in making decisions, judges adhere to their conscience. Progressive law is very important to be presented as a philosophical and theoretical basis for judges in handling cases in court. Judges have the freedom of logic to find and create laws that are in accordance with the community's sense of justice, because the law is for humans, not the other way around. The discovery of law in the context of making decisions, is not merely legalistic, does not only fulfill legal formalities or just maintains order, has a vision of foresight (visionary) who has the moral courage to make legal breakthroughs, and takes sides and is sensitive to fate and the state of the nation and state.